(untitled) (Chemical Engineering Research Bulletin, 2010)
The Claus process has been known and used in the industry for over 100 years. It involves thermal oxidation of hydrogen sulfide and its reaction with sulfur dioxide to form sulfur and water vapor. This process is equilibrium-limited and usually achieves efficiencies in the range of 94-97%, which have been regarded as acceptable in the past years. First bed operates at the temperature of 573 K, second and third beds operate at 523K and 473K. Outlet of each bed enters the condenser. Operating temperature of each condenser is about 413K which sulfur condenses in them. In this study catalytic bed process of sulfur recovery unit has been mathematically modeled and by MATLAB software simulated, and then output conditions of compounds has been calculated. Keywords: Sulfur recovery; Claus process; catalytic beds; modeling; simulation DOI = 10.3329/cerb.v14i2.5595 Chemical Engineering Research Bulletin 14 (2010) 110-114